Common mental disorder is associated with periodontitis. (28th October 2019) - Coelho, Julita Maria F.; Miranda, Samilly S.; da Cruz, Simone S.; dos Santos, Darci N.; Trindade, Soraya C.; Cerqueira, Eneida de M. M.; Passos‐Soares, Johelle de S.; Costa, Maria da Conceição N.; Figueiredo, Ana Claudia M. G.; Hintz, Alexandre Marcelo; de Almeida, Alba R. B.; Pereira, Monalisa N.; et al.
Abstract: Objectives: This research evaluated the association between exposure to common mental disorder (CMD) and the presence of periodontitis. Background: Common mental disorder is characterized by the presence of irritation, fatigue, insomnia, forgetfulness, decreased ability to concentrate, anxiety, and depression. It has been associated with several diseases; however, there are few studies that have associated it with periodontitis. Methods: This cross‐sectional study was carried out with 621 individuals. Data collection involved the application of a general questionnaire and the self‐reporting questionnaire for diagnosis of CMD. The diagnosis of periodontitis involved a full mouth periodontal examination using: clinical attachment level, probing depth, and bleeding on probing. Prevalence ratios and 95% confidence intervals between CMD (exposure) and periodontitis (outcome) were obtained. Results: In the final sample, 38.16% (237) of the individuals were classified with CMD. Among these, 28.27% (67) had periodontitis. Association measurements showed that the occurrence of periodontitis among those exposed to CMD is approximately 50% higher than in those without this mental condition, with statistical significance, after adjustment for age, sex, family income, current smoking habit, alcohol beverage consumption, and cardiovascular disease (PRadjusted  = 1.54, 95% CI: [1.13 to 2.10]). Conclusions: The findings showed a positive association between exposure to CMD and periodontitis, revealing the importance of broadening public actions targeting mental health, which seems to be related to oral health, mainly due to the high frequency of the diseases in the studied sample.